Stable oxygen isotope and flux partitioning demonstrates understory of an oak savanna contributes up to half of ecosystem carbon and water exchange - Dubbert, Maren; Piayda, Arndt; Cuntz, Matthias; Correia, Alexandra C.; Costa e Silva, Filipe; Pereira, Joao S.; Werner, Christiane (Frontiers in Plant Science, 2014)
Semi-arid ecosystems contribute about 40% to global net primary production (GPP) even though water is a major factor limiting carbon uptake. Evapotranspiration (ET) accounts for up to 95% of the water loss and in addition, vegetation can also mitigate drought effects by altering soil water distribution. Hence, partitioning of carbon and water fluxes between the soil and vegetation components is crucial to gain mechanistic understanding of vegetation effects on carbon and water cycling. However, the possible impact of herbaceous vegetation in savanna type ecosystems is often overlooked. Therefore, we aimed at quantifying understory vegetation effects on the water balance and productivity of a Mediterranean oak savanna. ET and net ecosystem CO2 exchange (NEE) were partitioned based on flux and stable oxygen isotope measurements and also rain infiltration was estimated. The understory vegetation contributed importantly to total ecosystem ET and GPP with a maximum of 43% and 51%, respectively. It reached water-use efficiencies (WUE; ratio of carbon gain by water loss) similar to cork-oak trees. The understory vegetation inhibited soil evaporation (E) and, although E was large during wet periods, it did not diminish WUE during water-limited times. The understory strongly increased soil water infiltration, specifically following major rain events. At the same time, the understory itself was vulnerable to drought, which led to an earlier senescence of the understory growing under trees as compared to open areas, due to competition for water. Thus, beneficial understory effects are dominant and contribute to the resilience of this ecosystem. At the same time the vulnerability of the understory to drought suggests that future climate change scenarios for the Mediterranean basin threaten understory development. This in turn will very likely diminish beneficial understory effects like infiltration and ground water recharge and therefore ecosystem resilience to drought.